1997
DOI: 10.1111/j.1530-0277.1997.tb03844.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption by Young Actively Growing Rats: A Study of Cortical Bone Histomorphometry and Mechanical Properties

Abstract: Alcohol consumption by young actively growing rats has been previously demonstrated to decrease cortical and cancellous bone density, to reduce trabecular bone volume, and to inhibit bone growth at the epiphyseal growth plate. This study addresses the action of alcohol on cortical bone growth using histomorphometric techniques and on mechanical properties by three-point bending. Four-week-old, female Sprague-Dawley rats were divided into three groups. Alcohol-treated animals were fed a modified Lieber-DeCarli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 14 publications
5
64
2
Order By: Relevance
“…The detrimental changes in cortical bone histomorphometry observed in rats fed alcohol were anticipated because of the well documented inhibition of periosteal and endocortical bone formation by ethanol in rapidly growing male and female rats Hogan et al, 1997;Turner et al, 1988;Sampson et al, 1996;Sampson et al, 1997b;Peng et al, 1988). The present study extends earlier work by showing that alcohol inhibits cortical bone formation in rats approaching skeletal maturity and by investigating the combined effects of alcohol and reduced weight bearing on cortical bone.…”
Section: Discussion Alcohol Clin Exp Ressupporting
confidence: 78%
See 2 more Smart Citations
“…The detrimental changes in cortical bone histomorphometry observed in rats fed alcohol were anticipated because of the well documented inhibition of periosteal and endocortical bone formation by ethanol in rapidly growing male and female rats Hogan et al, 1997;Turner et al, 1988;Sampson et al, 1996;Sampson et al, 1997b;Peng et al, 1988). The present study extends earlier work by showing that alcohol inhibits cortical bone formation in rats approaching skeletal maturity and by investigating the combined effects of alcohol and reduced weight bearing on cortical bone.…”
Section: Discussion Alcohol Clin Exp Ressupporting
confidence: 78%
“…Altered caloric intake was controlled for by pair-feeding the controls to alcohol-fed rats. Consistently, (Hogan et al, 1997;Turner et al, 1988;Sampson et al, 1996) alcohol leads to a further reduction in bone growth over and above that caused by caloric restriction. In contrast to growing rats, with proper acclimation, alcohol has minimal effects on food consumption and body weight in adults.…”
Section: Discussion Alcohol Clin Exp Resmentioning
confidence: 81%
See 1 more Smart Citation
“…These reductions in bone growth contribute to a decrease in bone mass. Similar changes were observed by Sampson and colleagues in growing female Sprague Dawley rats fed alcohol (Sampson et al 1996;Hogan et al 1997;Sampson et al 1997;Sampson & Spears 1999). Fig.…”
Section: Effects Of Alcohol On the Skeleton In Growing Ratssupporting
confidence: 75%
“…In rats, Nishiguchi et al [25] reported bone loss in different ages and sex [25]. Another two study examined the negative consequences of alcohol intake on cortical bone of mice and presented negative alterations on thickness and porosity of cortical bone, as well as on density of trabecular structure [24,26].…”
Section: Discussionmentioning
confidence: 99%